Intersecções entre as capacidades de marketing, os tipos estratégicos e o grau de internacionalização de empresas multinacionais brasileiras - Cassol, Cristina Anita (2021)
Given the new market dynamics associated with the movement of economic integration between different markets pronounced by globalization, understanding how companies operate strategically in the competitive market becomes relevant and essential to achieving satisfactory performance. In this context, marketing theory suggests the possibility of adequacy between the characteristics of the marketing organization and the strategic type (VORHIES; MORGAN, 2003), with this, the prerogative of establishing an integrated management emerges, that is, aligning the strategic behavior (MILES; SNOW, 1978) to marketing actions catalyzed by marketing capabilities (MORGAN; VORHIES; MASON, 2009; MORGAN; KATSIKEAS; VORHIES, 2012; MORGAN et al., 2018; MORGAN, 2019). Thus, the objective of this study is to analyze a convergence between marketing resources, the strategic type and the degree of internationalization of Brazilian multinational companies. The method is descriptive and the approach is qualitative. The collection was based on secondary data and the companies listed in the FDC Ranking of Brazilian Multinationals (2018) were used as population. For the final collection, four companies belonging to the B2C market were used, considering a market that meets the objectives of the study. Therefore, from the results presented, it is inferred that there is a relationship between marketing capabilities and strategic behavior and that this relationship has a certain influence on the degree of internationalization to a greater or lesser extent, possibly because all the companies analyzed demonstrated great power of internationalization in recent years, given the trajectory of internationalization that started relatively recently and the current promising directions they are taking. In thesis, these events may have been leveraged by internationalization strategies based in part on marketing capabilities, that is, on marketing resources leveraged and materialized by capabilities and the way in which they strategically position themselves. to target markets, that is, the behavior they adopt, be it more cautious, with incremental movements (analyst) or more audacious, with emphasis on leadership and domain of products/markets (prospector).